(untitled) (Indian Journal of Arid Horticulture, 2025)
A field experiment was conducted during 2004-09 to study the effect of soil water conservation practices viz., FYM mulch (@30 t/ha), cluster bean (Cyamopsis tetragonoloba) straw mulch (@8 t/ha), bui (Aerva pseudotomentosa) grass sraw mulch (@ 8 t/ha), sub-surface application of FYM (@ 12 t/ha) on soil properties. The soil samples were collected after the harvest of brinjal crop in January each year. The pooled data of five years were analysed for various soil physicochemical properties. Among various soil moisture conservation practices application of FYM mulch was found superior than others. It improved soil hydraulic conductivity from 29.35 in control to 27.12 cm h’, soil moisture content at field capacity from 3.30 to 3.88% w/w, wilting point from 1.20 to 1.54% w/w, organic carbon from 0.38 to 2.41 g kg’, available N from 78 to 120 kg ha ’, P from 8.16 to 13.74 kg ha’, K from 430 to 621 kg ha’, available Fe from 4.1 to 7.1 mg kg’, Mn from 4.5 to 6.5 mg kg’, Cu from 0.13 to 0.34 mg kg’ and Zn from 0.08 to 0.30 mg kg".